Effect of Biologic Therapy on Clinical and Laboratory Features of Macrophage Activation Syndrome Associated With Systemic Juvenile Idiopathic Arthritis. Issue 3 (30th January 2018) - Schulert, Grant S.; Minoia, Francesca; Bohnsack, John; Cron, Randy Q.; Hashad, Soah; KonÉ‐Paut, Isabelle; Kostik, Mikhail; Lovell, Daniel; Maritsi, Despoina; Nigrovic, Peter A.; Pal, Priyankar; Ravelli, Angelo; et al.
Abstract : Objective: To assess performance of the 2016 macrophage activation syndrome (MAS) classification criteria for patients with systemic juvenile idiopathic arthritis (JIA) who develop MAS while treated with biologic medications. Methods: A systematic literature review was performed to identify patients with MAS while being treated with interleukin (IL)‐1 and IL‐6 blocking agents. Clinical and laboratory information was compared to a large previously compiled historical cohort. Results: Eighteen publications were identified, and after removing duplicates, 35 patients treated with canakinumab and 49 patients with tocilizumab were available for analysis; 5 anakinra‐treated patients were excluded due to limited numbers. MAS classification criteria were less likely to classify tocilizumab‐treated patients as having MAS compared to the historical cohort or canakinumab‐treated patients (56.7%, 78.5%, and 84%, respectively; P < 0.01). Patients who developed MAS while treated with canakinumab trended towards lower ferritin at MAS onset than the historical cohort (4, 050 versus 5, 353 ng/ml; P = 0.18) but had no differences in other cardinal clinical or laboratory features. In comparison, patients who developed MAS while treated with tocilizumab were less likely febrile and had notably lower ferritin levels (1, 152 versus 5, 353 ng/ml; P < 0.001). Other features of MAS were more pronounced in patients treated with tocilizumab, including lower platelet counts, lower fibrinogen, and higher aspartate aminotransferase levels. Mortality rates for patients with MAS treated with tocilizumab or canakinumab were not significantly different from the historical cohort. Conclusion: These findings show substantial alterations in MAS features that may limit utility of defined criteria for diagnosis of systemic JIA patients treated with biologic agents.